Help please! <3 Simplify the expression to find the correct answer. Show your work and explain how you got that answer. [tex]\frac{1}{3}\sqrt{21}-\frac{2}{3}\sqrt{3} x \sqrt{7}[/tex] A. [tex]-\frac{1}{3}\sqrt{21}[/tex] B. [tex]\frac{2}{3}\sqrt{21}[/tex] C. [tex]\frac{2}{3}\sqrt{18×7}[/tex] D. [tex]-\frac{1}{3}\sqrt{63}x\sqrt{7}[/tex]

Respuesta :

Answer:

-1/3 sqrt(21)

Step-by-step explanation:

1/3 sqrt(21) - 2/3 sqrt(3)  * sqrt(7)

We know sqrt(a) * sqrt(b) = sqrt(ab)

1/3 sqrt(21) - 2/3 sqrt(21)

Factor out sqrt(21)

sqrt(21) (1/3-2/3)

sqrt(21) (-1/3)

-1/3 sqrt(21)

Answer: Choice A)  [tex]-\frac{1}{3}\sqrt{21}[/tex]

=====================================================

Work Shown:

I'm guessing that the x you wrote is to signify multiplication. If so, then one way to do the steps is shown in the attached image below.

In step 2, I used the rule that sqrt(x)*sqrt(y) = sqrt(x*y).

Ver imagen jimthompson5910